Effects of Multimedia Audio and Video Integrated Orientation Training on Employees’ Organizational Identification and Self-Efficacy Promotion - Huang, Ling-Chuan; Hung, Chao-Yang (Frontiers in Psychology, 2022)
This study investigates the instructional effectiveness of multimedia audio and video integrated pre-service education. In addition, the effects of pre-service education on organizational identification and self-efficacy promotion are discussed in this study. The participants of the study consist of 264 supervisors and employees in the high-tech industry. The results revealed statistically significant positive effects of pre-service education on employees’ organizational identification and self-efficacy. The effect of employees’ organizational identification on self-efficacy promotion was also significantly positive.